Understanding Antibiotic Use in Companion Animals: A Literature Review Identifying Avenues for Future Efforts - Tompson, Alice C.; Mateus, Ana L. P.; Brodbelt, Dave C.; Chandler, Clare I. R. (Frontiers in Veterinary Science, 2021)
Addressing antibiotic use is essential to tackle antimicrobial resistance, a major human and animal health challenge. This review seeks to inform stewardship efforts in companion animals by collating research insights regarding antibiotic use in this group and identifying overlooked avenues for future research and stewardship efforts. The development of population-based methods has established that antibiotics are frequently used in companion animal care. Research insights are also contributing toward an in-depth comprehension of the contexts to antibiotic use. Qualitative approaches, for example, have enabled a nuanced understanding in four key areas: interactions with owners, clinical and financial risk management, time pressures, and clinic dynamics. This review identifies that much of the existing research frames antibiotic use as the result of choices made by the individuals at the interface of their use. Future research and policy endeavours could look beyond the moment of prescribing to consider the societal structures and networks in which companion animal antibiotic use is entangled. A diversification in research approaches and frameworks through which antibiotic use is understood will facilitate the identification of additional targets for stewardship initiatives beyond providing information and awareness campaigns.